THE RELATIONSHIP BETWEEN SELF-EFFICACY, MOTIVATION, AND SPEAKING ABILITY AMONG FOURTH SEMESTER STUDENTS - Sakinah Hubaib (Didascein : Journal of English Education, 2025)
This study aimed to address three objectives: the connection between self-efficacy and speaking skills, the link between motivation and speaking skills, and the simultaneous relationship among self-efficacy, motivation, and speaking skills. The researcher conducted a form of oral assessment to collect data on students' speaking skills. Meanwhile, to collect students’ self-efficacy and motivation, the researcher conducted questionnaires. Every student among the 38 samples was requested to deliver their presentation to the class. The obtained data were analyzed using correlational analysis run by SPSS. The results of the research revealed that there was a statistically significant relationship between self-efficacy and speaking ability (p < 0.05), as well as between motivation and speaking ability (p < 0.05). Furthermore, a significant overall relationship was found among self-efficacy, motivation, and speaking ability (F < 0.05). There was a notable relationship among self-efficacy, motivation, and speaking ability, with F < 0.05. The research findings indicated that both lecturers and students of the English Department at Kutai Kartanegara should focus more on efficacy and motivation. Additionally, the future researcher is encouraged to conduct a more in-depth observation involving a larger population and diverse research instruments in a related study or to implement teaching methods that boost students’ confidence and motivation in speaking classes.